Architecture as a driver for the athletic performance enhancement of professional swimmers at the University of Pretoria, TuksSport - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2022)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2021.